The Lived Experience of Suffering by Nigerian Female Breast Cancer Survivors: A Phenomenological Perspective - Chinomso Ugochukwu Nwozichi PhD, RN, CMSRN, OCN, FAAN; Margaret Olutosin Ojewale PhD, RN; Omolabake Salako BSN, RN; Deliverance Brotobor MSc, RN; Elizabeth Olaogun MSc, RN (Journal of Patient Experience)
Breast cancer is a significant public health concern globally, and its impact extends beyond physical survival. Survivors often grapple with a myriad of challenges, including psychological distress, social isolation, and financial hardship. These challenges are often exacerbated in low-resource settings like Nigeria, where limited access to quality healthcare, socioeconomic disparities, and cultural stigma surrounding cancer can significantly impact the quality of life for survivors. This study aims to explore the suffering perceived by long-term breast cancer survivors in Nigeria, focusing on their lived experiences during and after treatment. Using a phenomenological approach, in-depth interviews were conducted with 22 women who have survived breast cancer for over 5 years. Data were analyzed using thematic analysis to capture the essence of their suffering, allowing for a deep understanding of their lived experiences. Five main domains emerged: (1) Physical Suffering, (2) Emotional Distress, (3) Social Suffering, (4) Financial Strain, and (5) Spiritual and Resilient Coping. Participants described their suffering as a multifaceted journey marked by physical pain, emotional turmoil, social stigma, financial challenges, and resilience fostered through spirituality and support systems. The phenomenological analysis revealed that the participants’ suffering extended beyond the physical, touching every aspect of their lives and reshaping their identities and perceptions of self. The findings highlight the complex nature of suffering among breast cancer survivors in Nigeria, underscoring the need for comprehensive survivorship care that addresses physical, psychosocial, and spiritual dimensions. By understanding the essence of their suffering, healthcare providers can develop more compassionate, context-specific care strategies that validate and support the holistic needs of survivors.